Translation and cross-cultural adaptation of the Scleroderma Health Assessment Questionnaire to Brazilian Portuguese - Orlandi, Aline Cristina; Cardoso, Fernanda Pontes; Santos, Lucas Macedo; Cruz, Vaneska da Graça; Jones, Anamaria; Kyser, Cristiane; Natour, Jamil (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: Systemic sclerosis is an autoimmune disease characterized by abnormalities of vascularization that may cause fibrosis of the skin and other organs and lead to dysfunction. It is therefore essential to have tools capable of evaluating function in individuals with this condition. The aim of this study was to translate the Scleroderma Health Assessment Questionnaire (SHAQ) into Portuguese, adapt it to Brazilian culture and test its validity and reliability. DESIGN AND SETTING: The validation of SHAQ followed internationally accepted methodology, and was performed in university outpatient clinics. METHODS: SHAQ was translated into Portuguese and back-translated. In the cultural adaptation phase, it was applied to 20 outpatients. Items not understood by 20% of the patients were modified and applied to another 20 outpatients. Twenty patients were interviewed on two different occasions to determine the validity and reliability of the questionnaire: two interviewers on the first occasion and one interviewer 14 days later. To determine the external validity, comparisons were made with Health Assessment Questionnaire (HAQ), Disabilities of the Arm, Shoulder and Hand (DASH) and short form-36 (SF-36). RESULTS: In the interobserver evaluation, Pearson’s correlation coefficient and the intraclass correlation coefficient were both 0.967. In the intraobserver evaluation, Pearson’s correlation coefficient was 0.735 and the intraclass correlation coefficient was 0.687. Regarding external validity, SHAQ scores were statistically correlated with all measurements, except the general health domain of SF-36 and the work-related score (Q2) of DASH. CONCLUSION: The Brazilian version of SHAQ proved to be valid and reliable for assessing function in patients with diffuse systemic sclerosis.